Protocol for the development of a global core outcome set for the surgical treatment of differentiated thyroid cancer: a literature review and international Delphi survey - Anton F Engelsman; Romana T Netea-Maier; Christiaan F Mooij; Robin P Peeters; Menno R Vriens; A S Paul van Trotsenburg; Schelto Kruijff; Joep P M Derikx; Faridi S Jamaludin; Daniël J van de Berg; Hanneke M van Santen; Sarah C Clement; et al. (BMJ Open)
Introduction There is a lack of consensus on the optimal surgical strategy for differentiated thyroid cancer (DTC), partly due to inconsistent reporting of outcomes. This limits the ability to compare study results, hindering the ability to draw conclusions regarding novel treatment strategies. The development of a core outcome set (COS) reduces heterogeneity in the selection and reporting of clinical trial outcomes. Currently, there is no COS for the surgical treatment of DTC. We aim to reach a global consensus among patients and physicians on the COS for the surgical treatment for patients with DTC of all ages.Methods and analysis The DTC-COS development will consist of three phases: first, an extensive literature review will be performed to identify reported outcomes in studies regarding surgical treatment for DTC in patients of all ages. Second, a 2-step or 3-step Delphi procedure will be performed to identify a final set of core outcomes out of the selected outcomes from the literature review. For this Delphi survey, both healthcare professionals and patients will be invited. Third, an (online) expert meeting with participants from every stakeholder group is organised to ratify the final core outcome set. The final COS will be reported in accordance with the COS-Standards for Reporting statement.Ethics and dissemination The medical research ethics committee of the Amsterdam UMC confirmed that the Dutch Medical Research Involving Human Subjects Act (WMO) does not apply to this study and that full approval by the committee is not required. The study is registered in the COMET initiative database (registration number 2597). Results will be presented in peer-reviewed academic journals and at (international) conferences.Trial registration number COMET initiative database 2597